To run or not to run intentions of politicians to participate in politics. - Bautista, Michelle M. (2016.)
The overall purpose of the study was to investigate the intentions of Filipino politicians to participate in politics, guided by Icek Ajzen?s Theory of Planned Behavior. The study employed qualitative methodology involving a total of 10 interviews with political candidates from province of Aklan. Participants were recruited using criterion sampling. Results showed that attitude towards political participation, perceived pressure from the public, political parties and family members, belief in one?s capacity to pursue political activities, and past experience largely influence the intentions of politicians to engage in politics; and their intentions, in turn, were translated into actual political participation. Past experience and belief in one?s capacity to pursue political activities were found to directly influence political engagement and all identified factors were also found to be associated with one another. The relationships of all the constructs were consistent with our modified model of the Theory of Planned Behavior. Overall, the study offered support to the use of qualitative methodology in utilizing the Theory of Planned Behavior as a theoretical framework. The study also provided evidence that past experience could be included in the model of the Theory of Planned Behavior.
Research Paper (Undergraduate, Bachelor of Arts in Psychology-Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Filipino Politicians -- Research